1999
DOI: 10.1002/(sici)1096-9861(19991220)415:3<285::aid-cne1>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Expression in Rat Brain: Evidence Against a Pervasive Relationship of Urocortin‐Containing Projections With Targets Bearing Type 2 CRF Receptors

Abstract: Histochemical and axonal transport methods were used to clarify the central organization of cells and fibers that express urocortin (UCN), a recently discovered corticotropin-releasing factor (CRF)-related neuropeptide, which has been proposed as an endogenous ligand for type 2 CRF receptors (CRF-R2). Neurons that display both UCN mRNA and peptide expression were found to be centered in the Edinger-Westphal (EW), lateral superior olivary (LSO), and supraoptic nuclei; lower levels of expression are seen in cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
173
1
13

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(202 citation statements)
references
References 0 publications
15
173
1
13
Order By: Relevance
“…Anatomical tract-tracing studies indicate reciprocal connections between the amygdala and lateral septum (Meibach and Siegel 1977;Staiger and Nurnberger 1991), and several studies suggest that the lateral septum inhibits the amygdala (Lee et al 1988;Melia et al 1991). Both the lateral septum and amygdala receive CRF and urocortin 1-positive terminals (Swanson et al 1983;Sakanaka et al 1988;Kozicz et al 1998;Bittencourt et al 1999). Footshock-induced behavior is reduced by intra-lateral septum infusion of α-helical CRF (9-41) but not NBI27914, a selective CRF 1 antagonist, and it is also reduced by intra-amygdala infusion of NBI27914 (Bakshi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical tract-tracing studies indicate reciprocal connections between the amygdala and lateral septum (Meibach and Siegel 1977;Staiger and Nurnberger 1991), and several studies suggest that the lateral septum inhibits the amygdala (Lee et al 1988;Melia et al 1991). Both the lateral septum and amygdala receive CRF and urocortin 1-positive terminals (Swanson et al 1983;Sakanaka et al 1988;Kozicz et al 1998;Bittencourt et al 1999). Footshock-induced behavior is reduced by intra-lateral septum infusion of α-helical CRF (9-41) but not NBI27914, a selective CRF 1 antagonist, and it is also reduced by intra-amygdala infusion of NBI27914 (Bakshi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the reason, the effects in many of these regions agree with the connections of the EW nucleus and have allowed the development of a hypothetical neurocircuit. Thus, in rodents EW has been shown to send urocortin projections to the LSD/LSI border region (Bittencourt et al 1999). Interestingly, this region is also known to have high levels of CRF-R2 mRNA expression (Van Pett et al 2000).…”
Section: Ethanol and Suppression Of C-fos Expressionmentioning
confidence: 99%
“…However, evidence is accumulating that EW is involved in other functions, including temperature regulation, nociception and anxiety (Loewy et al 1978;Innis and Aghajanian 1986;Smith et al 1998;Weninger et al 1999). Moreover, EW is the main brain source of the neuropeptide urocortin, the alternative and strongest ligand of CRF receptors (Vaughan et al 1995;Bittencourt et al 1999). Our recent studies using inbred mouse strains suggest that urocortin-containing neurons of EW are involved in regulation of ethanol-induced hypothermia and alcohol consumption in mice (Bachtell et al 2002).…”
Section: Ethanol and Induction Of C-fos Expressionmentioning
confidence: 99%
“…We have also previously observed that the presence of Ucn1 immunoreactivity in its projection areas does not always parallel the expression of Ucn1 in EW Weitemier and Ryabinin 2004). Therefore, the present study also examines Ucn1 immunoreactivity in these rat lines in the lateral septum, a major projection area of Ucn1-positive neurons (Bittencourt et al 1999). We hypothesize that in either EW or LS, or possibly in both, Ucn1 levels will be higher in alcohol-preferring vs nonpreferring animals.…”
Section: Introductionmentioning
confidence: 96%
“…The EW has long been thought to be a cholinergic nucleus associated with oculomotor function (Warwick 1954;Klooster et al 1993). However, recent evidence from studies in rat, monkey, and bird suggests that the area broadly defined as the EW can be subdivided into two populations of neurons: one cholinergic that projects to the ciliary ganglion and one urocortinergic that projects to several brain regions including the lateral septum (LS), dorsal raphe, and spinal cord (Bittencourt et al 1999;Cavani et al 2003;Vasconcelos et al 2003).…”
Section: Introductionmentioning
confidence: 99%